Pro-Kontra Pengaruh Filsafat Terhadap Nahwu - Wanda Alfina; Mia Aulia; Rissa Rahmadaniati; Ghaiza Insan Kamila (PT. Hasba Edukasi Mandiri, 2025)
This study discusses the pros and cons of the influence of philosophy in the development of nahwu, one of the main branches of Arabic grammar. The birth of nahwu was initially practical to maintain the purity of Arabic from errors, especially in understanding Islamic texts. However, along with the development of the era, the influence of philosophy, especially Greek logic, began to color the compilation of nahwu rules. This study aims to reveal the forms of philosophical influence in nahwu, as well as to examine the arguments of those who support and reject it. The results of the study show that the philosophical approach provides a logical structure in grammatical discussions, but is also considered to complicate learning at the basic level. This study also highlights the direct implications of the pros and cons on the nahwu teaching system in the modern era. With a qualitative approach through literature studies and discourse analysis, this study recommends a synthesis between philosophical and practical approaches in nahwu learning to be more contextual, effective, and adaptive to the needs of today's students.